Toxicity of isoproturon on Saccharomyces cerevisiae growing in mineral medium depends on glutathione-mediated antioxidant capacity. - Candeias, M (2011)
The results revealed an increase of viable cells, after 72 h of culture and an increase of antioxidant power mediated by GSH and GR activity in S. cerevisiae UE-ME3. The adaptive response of UE-ME3 strain to isoproturon, determined in MB, was clearly higher than observed in IGC-3507 strain. So, we presume that the extent of the toxic effect of isoproturon in both yeast strains depends on glutathione-mediated antioxidant capacity.